Kesalehan Sosial Masyarakat Muslim Indramayu: Kajian Living Hadits Tentang Bertetangga - Nurkholis Sofwan (Al Ashriyyah, 2018)
This paper describes the social piety of the Prophet which is applied by the Muslim community Indramayu in the life of neighbors. In the hadith dicipline, it is called ‘living hadith’. Most Muslim scholars argue that if someone has faith and submit to God, then he would also be compassionate toward others, and even perceive others as his brother. While others argue that religious piety contained in a person is not always in line with the social piety in his life. Therefore, the hadith of the Prophet of neighborliness understood by the Muslim community Indramayu is one instrument that is significant enough to test the validity of those two opinions. It was concluded that the public piety Indramayu basically in line with the hadith of the Prophet about the neighbors; which gives debts to the neighbors, help, visit neighbors who are sick, administer and deliver the dead bodies of his neighbors, and give each other food at certain moments. So this proves that individual piety is directly proportional to the social piety.